2022
DOI: 10.1002/jcla.24643
|View full text |Cite
|
Sign up to set email alerts
|

The potency of common proinflammatory cytokines measurement for revealing the risk and severity of anxiety and depression in psoriasis patients

Abstract: Objective Proinflammatory cytokines mediate anxiety and depression in various ways, such as immunity, inflammation, and the hypothalamic–pituitary–adrenal axis. This study intended to further explore the linkage of common proinflammatory cytokine levels with anxiety and depression in psoriasis patients. Methods Totally, 150 psoriasis patients and 50 healthy controls (HCs) were included; the serum samples were collected, then common proinflammatory cytokines were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…20,35,50 Although there is no correlation between IL-6 level and disease activity, studies have confirmed that patients with psoriasis have significantly increased serum IL-6 levels and overexpression in psoriatic lesions versus healthy controls. 51,52 In this study, we found that plasma IL-6 levels were higher in patients with psoriasis than in healthy populations and were abnormally expressed in psoriatic lesions and imiquimod-induced psoriasis-like lesions. Interestingly, IL-6 expression was significantly increased in psoriatic lesions consistent with LMO4 overexpression in the present study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…20,35,50 Although there is no correlation between IL-6 level and disease activity, studies have confirmed that patients with psoriasis have significantly increased serum IL-6 levels and overexpression in psoriatic lesions versus healthy controls. 51,52 In this study, we found that plasma IL-6 levels were higher in patients with psoriasis than in healthy populations and were abnormally expressed in psoriatic lesions and imiquimod-induced psoriasis-like lesions. Interestingly, IL-6 expression was significantly increased in psoriatic lesions consistent with LMO4 overexpression in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…IL‐6 is another important member of the cytokine network that regulates keratinocyte proliferation and differentiation in psoriasis 20,35,50 . Although there is no correlation between IL‐6 level and disease activity, studies have confirmed that patients with psoriasis have significantly increased serum IL‐6 levels and overexpression in psoriatic lesions versus healthy controls 51,52 . In this study, we found that plasma IL‐6 levels were higher in patients with psoriasis than in healthy populations and were abnormally expressed in psoriatic lesions and imiquimod‐induced psoriasis‐like lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have analyzed the psychological status of middle-aged and young patients with dermatosis; generally, young patients pay more attention to appearance, and their emotional state is more linked to changes in appearance ( 20 ). It was reported that old patients with skin pruritus mostly showed type A behavior, who were prone to being nervous and anxious, and were not able to cope with this situation ( 21 , 22 ). Pruritus is an unpleasant feeling of the skin or mucous membrane that causes a desire to scratch.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent IL-17 production can induce the production of these same proinflammatory cytokines in an inflammatory mechanistic loop. 104 Furthermore, the IL-17 receptor is present on many cell types in the CNS, including endothelial cells of the BBB. Circulating IL-17 can bind to IL-17 receptors and affect expression of tight junctions and cell adhesion molecules on endothelial cells of the BBB, resulting in architectural changes.…”
Section: Oth Er E L E M E N Ts Th At M Ay I N F Lu E Nce M E N Ta L S...mentioning
confidence: 99%